2007
DOI: 10.29309/tpmj/2007.14.01.3633
|View full text |Cite
|
Sign up to set email alerts
|

Rubber Banb Ligation

Abstract: Objectives: To find out the post-operative complications of rubber band ligation in 2nd and 3rd degree of hemorrhoids. Design: A descriptive study. Place and Duration of study: An eighteen month study with 2 months follow up (from January 2002 to June 2003), conducted in the department of surgery, Allied Hospital Faisalabad. Patients and Methods: 50 patients were selected (from OPD) in this study. We included all patients with uncomplicated, primary 2nd and 3rd degree hemorrhoids, above 12 years of age and hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This conforms to Watson et al who found that 65% of patients complained of per-rectal bleeding on the day following operation 15 . In the case series by Bhutta et al and Dilawaiz et al, only 6-12% of patients complained of per-rectal bleeding immediately following the procedure 16,17 . Those studies also carried out banding as an outpatient procedure, however, limitations in the follow-up of the patients probably accounted for the fewer patients who came back with complaints of per-rectal bleeding.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This conforms to Watson et al who found that 65% of patients complained of per-rectal bleeding on the day following operation 15 . In the case series by Bhutta et al and Dilawaiz et al, only 6-12% of patients complained of per-rectal bleeding immediately following the procedure 16,17 . Those studies also carried out banding as an outpatient procedure, however, limitations in the follow-up of the patients probably accounted for the fewer patients who came back with complaints of per-rectal bleeding.…”
Section: Discussionmentioning
confidence: 95%
“…Various other authors in our population show male predominance in haemorrhoid patients [8][9][10] . However, western literature showed an equal or mixed male or female predominance pattern in haemorrhoid disease [11][12][13][14][15][16][17] . This could be due to different hospital setup, social, cultural values and eating habits.…”
Section: Discussionmentioning
confidence: 99%